2018
DOI: 10.1016/j.anpsic.2018.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the Catalan version of DS14 scale for assessing Type-D personality

Abstract: This study was designed to check the psychometric properties of an online Catalan version of the Type D Personality Scale-14 (DS14). Participants were 600 subjects including university professors, service and administrative personnel (n = 419) and students (n = 181); in total 196 men (32.7%) and 404 women (67.3%) with a mean age of 36.99 (SD = 12.76). The sample was randomly split in two groups: calibration and validation. The structural validity was analyzed in the calibration group (n = 311) using explorator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…In the study by Denolt, Vanflius, Lauder, Mamrastig, Gowartz, Pasmirs et al (2018), the results indicated that personality type D has an adverse effect on endothelial (intravascular) dysfunction in patients with coronary arteries. Aluja et al (2019) and Malas et al (2018) showed in their research that among personality dimensions, type D personality type is a strong predictor of heart diseases. They showed that using the D personality scale can be useful and practical to distinguish people with high risk of coronary heart disease from healthy people.…”
Section: Introductionmentioning
confidence: 99%
“…In the study by Denolt, Vanflius, Lauder, Mamrastig, Gowartz, Pasmirs et al (2018), the results indicated that personality type D has an adverse effect on endothelial (intravascular) dysfunction in patients with coronary arteries. Aluja et al (2019) and Malas et al (2018) showed in their research that among personality dimensions, type D personality type is a strong predictor of heart diseases. They showed that using the D personality scale can be useful and practical to distinguish people with high risk of coronary heart disease from healthy people.…”
Section: Introductionmentioning
confidence: 99%